APPLICATION OF INTERACTIVE METHOD AMONG PEDAGOGUES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The interactive method in education has garnered significant attention for its potential to enhance learning outcomes by promoting active participation and engagement among students. This study examines the application of interactive methods among pedagogues, focusing on their effectiveness in fostering a dynamic and collaborative learning environment. Through a comprehensive review of literature and analysis of case studies, the research aims to provide insights into the practical implementation of interactive techniques in pedagogical settings. The findings suggest that interactive methods not only improve student motivation and understanding but also support the development of critical thinking and problem-solving skills. The study concludes with recommendations for educators on integrating interactive methods into their teaching practices to maximize educational benefits.